‘From bones to burnout, delving beyond the scalpel’: prioritizing surgeon wellness for optimal patient outcomes - Ganesh, Arjun; Kumar, M. Mohan (International Journal of Research in Orthopaedics, 2023)
Orthopaedic surgeons face significant challenges in balancing their demanding professional responsibilities with their personal lives, which can often lead to burnout and poor well-being. Orthopaedic surgeons face a variety of multifaceted stressors which lead to burnout and have significant impacts on their well-being and the quality of patient care. Here, we present an overview of relevant literature and provide evidence-based recommendations for a comprehensive multidisciplinary approach to implement strategies to mitigate their effects.